Lanthanide metal coordination polymer as well as preparation method and application thereof
Through the preparation and application of the lanthanide metal coordination polymer [Gd(piac)2(H2O)2]n or [Tb(piac)2(H2O)2]n, the deficiencies in the detection of Cu2+ and photocatalytic organic dyes in water in the prior art are solved, and efficient fluorescence ion detection and photocatalytic degradation effects are achieved.
Patent Information
- Application Number
- CN202510104402.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-23
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-01-23
AI Technical Summary
The prior art has problems such as long detection time, expensive equipment and high coordination number of lanthanide metal ions in detection of Cu2+ and photocatalytic organic dye degradation in water, resulting in relatively few studies.
This type of coordination polymer is prepared by a one-pot hydrothermal reaction using the lanthanide metal coordination polymer [Gd(piac)2(H2O)2]n or [Tb(piac)2(H2O)2]n for fluorescence ion detection and photocatalytic dye degradation.
High selectivity and high sensitivity detection of Cu2+ is achieved, and good photocatalytic degradation effect on organic dyes RhB and MO, simplifying the preparation process and improving yield.
Smart Images

Figure CN119875138A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of fluorescence sensing technology and photocatalytic organic dye degradation, and in particular to a lanthanide metal coordination polymer and a preparation method and application thereof. Background Art
[0002] With the development of social industry, many metal ions are released through industrial wastewater, endangering people's health and life, especially Cu 2+ The main source of copper intake for the human body is daily diet. Copper ions can accumulate through the food chain and eventually enter the human body. Excessive intake of copper ions can cause harm to the body, such as kidney damage, liver necrosis and nerve damage. Therefore, it is necessary to establish an effective detection method for Cu in water. 2+ A sustainable approach is essential to protecting ecosystems and human health.
[0003] Most of the current detection technologies require long processing time and expensive equipment. Fluorescence sensing technology has been studied because of its high sensitivity, easy operation, fast response, high selectivity and low cost. At present, many coordination polymers have been developed for the detection of heavy metal ions, such as Pb(II), Hg(II), Cr(II), Co(II) and Cu(II). At the same time, small organic molecules such as nitrobenzene, acetone and chloroform can also be detected. However, most of the reported probe molecules are based on transition metal complexes. Although lanthanide metal complexes have unique advantages such as narrow emission spectra, high optical stability and biodegradability, they are relatively less studied due to the high coordination number of lanthanide metal ions. Therefore, the construction of fluorescent probes based on rare earth complexes remains an important focus of current research.
[0004] Likewise, the emission of organic dye pollutants is another threat to ecosystems and human health. The persistence and high toxicity of these dyes make them not easily degradable. The degradation of these dyes is achieved through photocatalysis, in particular using lanthanide metal-based coordination polymers as catalysts. Photocatalysts are activated by light and produce reactive oxygen species that are able to decompose complex dye molecules into simpler and less harmful compounds. Lanthanide metal coordination polymers show considerable potential in photocatalytic processes due to their unique structural and electronic properties that enhance light absorption and reactive oxygen production. The integration of fluorescence sensing with the photocatalytic system enables a single material to both detect and degrade organic pollutants. This innovative strategy greatly promotes the development of sustainable water treatment technologies. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide a lanthanide metal coordination polymer and its preparation method and application in view of the above-mentioned deficiencies in the prior art, wherein the lanthanide metal refers to gadolinium (III) or terbium (III), and the coordination polymers thereof are [Gd(piac)2(H2O)2] n or [Tb(piac)2(H2O)2] n The two coordination polymers are isomorphic two-dimensional structures. The two coordination polymers are centered on gadolinium (III) or terbium (III), forming an eight-coordinate structure, which is coordinated and connected by the ligand carboxyl oxygen atom to form a one-dimensional ring-chain structure, and the ring-chain structure is further bridged by the ligand to form a two-dimensional structure.
[0006] In order to solve the above technical problems, the present invention provides a lanthanide metal coordination polymer, wherein the chemical formula of the lanthanide metal coordination polymer is [Gd(piac)2(H2O)2] n or [Tb(piac)2(H2O)2] n The single molecular formulas of the lanthanide metal coordination polymers are C 22 H 17 N4O 10 Gd or C 22 H 17 N4O 10 Tb.
[0007] The present invention provides a method for preparing the above-mentioned lanthanide metal coordination polymer, comprising the following steps:
[0008] S1, dissolving 5-(1H-pyrazol-3-yl)isophthalic acid and a lanthanide metal salt in deionized water to obtain a mixed solution, adding a NaOH solution to adjust the pH value of the mixed solution, and then performing a hydrothermal reaction to obtain a reaction product;
[0009] S2. The reaction product obtained in S1 is cooled and crystallized naturally, and then washed and dried to obtain a lanthanide metal coordination polymer.
[0010] According to the preparation method of the lanthanide metal coordination polymer provided by the present invention, the lanthanide metal salt in S1 is Gd(NO3)3·6H2O or TbCl3·6H2O.
[0011] According to the method for preparing a lanthanide metal coordination polymer provided by the present invention, the molar ratio of 5-(1H-pyrazol-3-yl)isophthalic acid to lanthanide metal salt in S1 is 0.05-0.1 mmol: 0.1-0.15 mmol.
[0012] According to the method for preparing a lanthanide metal coordination polymer provided by the present invention, the pH value of the mixed solution in S1 is 5-7.
[0013] According to the preparation method of lanthanide metal coordination polymer provided by the present invention, the temperature of the hydrothermal reaction in S1 is 180°C, the temperature rising rate is 5-10°C / h, the hydrothermal reaction is carried out in a sealed reactor, and the hydrothermal reaction time is 3-5d.
[0014] According to the preparation method of the lanthanide metal coordination polymer provided by the present invention, the drying condition in S2 is: maintaining the temperature in a constant temperature drying oven at 60° C. for 3 hours.
[0015] The present invention also provides an application of the lanthanide metal coordination polymer. The lanthanide metal coordination polymer can be applied to the field of fluorescent ion detection and the field of photocatalytic dye degradation.
[0016] Compared with the prior art, the present invention has the following advantages:
[0017] (1) The present invention adopts a one-pot hydrothermal reaction to prepare a lanthanide metal coordination polymer, and the chemical formula of the lanthanide metal coordination polymer is [Gd(piac)2(H2O)2] n or [Tb(piac)2(H2O)2] n , whose molecular formulas are C 22 H 17 N4O 10 Gd or C 22 H 17 N4O 10 The preparation method has the advantages of simple process, convenient operation, high yield and good reproducibility.
[0018] (2) The lanthanide metal coordination polymer [Tb(piac)2(H2O)2] prepared by the present invention n , has good fluorescence properties, for Cu 2+ It exhibits high selectivity and sensitivity and can effectively detect Cu by fluorescence quenching. 2+ At the same time, the lanthanide metal coordination polymer [Gd(piac)2(H2O)2] prepared by the present invention n It has good photocatalytic performance and has good photocatalytic degradation effect on organic dyes RhB and MO. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 is the coordination environment diagram of terbium (III) in the terbium (III) coordination polymer;
[0020] Figure 2 is the one-dimensional structure diagram of terbium (III) coordination polymer;
[0021] Figure 3 This is a two-dimensional structure diagram of terbium (III) coordination polymer;
[0022] Figure 4 is the coordination environment diagram of gadolinium (III) in the gadolinium (III) coordination polymer;
[0023] Figure 5 is the one-dimensional structure diagram of gadolinium (III) coordination polymer;
[0024] Figure 6 Two-dimensional structure of gadolinium (III) coordination polymer;
[0025] Figure 7 is the powder X-ray diffraction pattern of terbium (III) coordination polymer and gadolinium (III) coordination polymer;
[0026] Figure 8 This is the emission spectrum of terbium (III) coordination polymer in different ions;
[0027] Fig. 9 This is a strength comparison diagram of terbium (III) coordination polymer in different ions;
[0028] Fig.10 is the absorption spectrum of gadolinium (III) coordination polymer to RhB and MO;
[0029] Fig.11 This is the degradation rate diagram of RhB and MO by gadolinium (III) coordination polymer. DETAILED DESCRIPTION
[0030] Example 1
[0031] This embodiment provides a method for preparing a lanthanide metal coordination polymer, and the specific steps are as follows:
[0032] S1. Dissolve 0.05 mmol of ligand 5-(1H-pyrazol-3-yl)isophthalic acid (H2piac) and 0.1 mmol of metal salt Gd(NO3)3·6H2O in 10 mL of deionized water to obtain a mixed solution, add NaOH solution to adjust the pH value of the mixed solution to 5, and then transfer the mixed solution to a high-pressure reactor. The temperature in the high-pressure reactor is increased to 180°C at a heating rate of 10°C / h, and a solvent thermal reaction is carried out for 5 days to obtain a reaction product.
[0033] The structural formula of H2piac is:
[0034]
[0035] S2. The reaction product obtained in S1 is cooled and crystallized naturally, and then washed with anhydrous ethanol and filtered under reduced pressure to obtain a white crystalline powder, which is placed in an oven at a temperature of 60° C. for 3 hours for drying to obtain a lanthanide metal coordination polymer, a gadolinium (III) coordination polymer [Gd(piac)2(H2O)2] n , with a yield of 37%.
[0036] Example 2
[0037] S1. Dissolve 0.1 mmol of ligand 5-(1H-pyrazol-3-yl)isophthalic acid and 0.1 mmol of metal salt Gd(NO3)3·6H2O in 10 mL of deionized water to obtain a mixed solution, add NaOH solution to adjust the pH value of the mixed solution to 5.5, and then transfer the mixed solution to a high-pressure reactor. After the temperature in the high-pressure reactor is increased to 180°C at a heating rate of 10°C / h, a solvothermal reaction is carried out for 3 days to obtain a reaction product.
[0038] S2. The reaction product obtained in S1 is cooled and crystallized naturally, and then washed with anhydrous ethanol and filtered under reduced pressure to obtain a white crystalline powder, which is placed in an oven at a temperature of 60° C. for 3 hours for drying to obtain a lanthanide metal coordination polymer, a gadolinium (III) coordination polymer [Gd(piac)2(H2O)2] n , with a yield of 41.1%.
[0039] Example 3
[0040] This embodiment provides a method for preparing a lanthanide metal coordination polymer, and the specific steps are as follows:
[0041] S1. Dissolve 0.1 mmol of ligand 5-(1H-pyrazol-3-yl)isophthalic acid and 0.1 mmol of metal salt TbCl3·6H2O in 10 mL of deionized water to obtain a mixed solution, add NaOH solution to adjust the pH value of the mixed solution to 6.3, and then transfer the mixed solution to a high-pressure reactor. After the temperature in the high-pressure reactor is increased to 180° C. at a heating rate of 10° C. / h, a solvent thermal reaction is carried out for 5 days to obtain a reaction product.
[0042] S2. The reaction product obtained in S1 is cooled and crystallized naturally, then washed with anhydrous ethanol and filtered under reduced pressure to obtain a white crystalline powder, which is placed in an oven at a temperature of 60° C. for 3 hours for drying to obtain a lanthanide metal coordination polymer, a terbium (III) coordination polymer [Tb(piac)2(H2O)2] n , with a yield of 75.6%.
[0043] Example 4
[0044] This embodiment provides a method for preparing a lanthanide metal coordination polymer, and the specific steps are as follows:
[0045] S1. Dissolve 0.1 mmol of ligand 5-(1H-pyrazol-3-yl)isophthalic acid and 0.1 mmol of metal salt TbCl3·6H2O in 10 mL of deionized water to obtain a mixed solution, add NaOH solution to adjust the pH value of the mixed solution to 5.5, and then transfer the mixed solution to a high-pressure reactor. After the temperature in the high-pressure reactor is increased to 180° C. at a heating rate of 10° C. / h, a solvent thermal reaction is carried out for 4 days to obtain a reaction product.
[0046] S2. The reaction product obtained in S1 is cooled and crystallized naturally, then washed with anhydrous ethanol and filtered under reduced pressure to obtain a white crystalline powder, which is placed in an oven at a temperature of 60° C. for 3 hours for drying to obtain a lanthanide metal coordination polymer, a terbium (III) coordination polymer [Tb(piac)2(H2O)2] n , with a yield of 55.6%.
[0047] Example 5
[0048] This embodiment provides a method for preparing a lanthanide metal coordination polymer, and the specific steps are as follows:
[0049] S1. Dissolve 0.1 mmol of ligand 5-(1H-pyrazol-3-yl)isophthalic acid and 0.15 mmol of metal salt Gd(NO3)3·6H2O in 10 mL of deionized water to obtain a mixed solution, add NaOH solution to adjust the pH value of the mixed solution to 6.3, and then transfer the mixed solution to a high-pressure reactor. After the temperature in the high-pressure reactor is increased to 180°C at a heating rate of 10°C / h, a solvent thermal reaction is carried out for 5 days to obtain a reaction product.
[0050] S2. The reaction product obtained in S1 is cooled and crystallized naturally, and then washed with anhydrous ethanol and filtered under reduced pressure to obtain a white crystalline powder, which is placed in an oven at a temperature of 60° C. for 3 hours for drying to obtain a lanthanide metal coordination polymer, a gadolinium (III) coordination polymer [Gd(piac)2(H2O)2] n , with a yield of 71.4%.
[0051] Example 6
[0052] This comparative example provides a method for preparing a lanthanide metal coordination polymer, and the specific steps are as follows:
[0053] S1. Dissolve 0.1 mmol of ligand 5-(1H-pyrazol-3-yl)isophthalic acid and 0.1 mmol of metal salt Gd(NO3)3·6H2O in 10 mL of deionized water to obtain a mixed solution, add NaOH solution to adjust the pH value of the mixed solution to 5.8, and then transfer the mixed solution to a high-pressure reactor. After the temperature in the high-pressure reactor is increased to 180°C at a heating rate of 10°C / h, a solvent thermal reaction is carried out for 5 days to obtain a reaction product.
[0054] S2. The reaction product obtained in S1 is cooled and crystallized naturally, and then washed with anhydrous ethanol and filtered under reduced pressure to obtain a white crystalline powder, which is placed in an oven at a temperature of 60° C. for 3 hours for drying to obtain a lanthanide metal coordination polymer, a gadolinium (III) coordination polymer [Gd(piac)2(H2O)2] n , with a yield of 54.8%.
[0055] Example 7
[0056] This comparative example provides a method for preparing a lanthanide metal coordination polymer, and the specific steps are as follows:
[0057] S1. Dissolve 0.1 mmol of ligand 5-(1H-pyrazol-3-yl)isophthalic acid and 0.1 mmol of metal salt TbCl3·6H2O in 10 mL of deionized water to obtain a mixed solution, add NaOH solution to adjust the pH value of the mixed solution to 5.8, and then transfer the mixed solution to a high-pressure reactor. After the temperature in the high-pressure reactor is increased to 180° C. at a heating rate of 10° C. / h, a solvent thermal reaction is carried out for 5 days to obtain a reaction product.
[0058] S2. The reaction product obtained in S1 is cooled and crystallized naturally, then washed with anhydrous ethanol and filtered under reduced pressure to obtain a white crystalline powder, which is placed in an oven at a temperature of 60° C. for 3 hours for drying to obtain a lanthanide metal coordination polymer, a terbium (III) coordination polymer [Tb(piac)2(H2O)2] n , with a yield of 51.6%.
[0059] Example 8
[0060] This comparative example provides a method for preparing a lanthanide metal coordination polymer, and the specific steps are as follows:
[0061] S1. Dissolve 0.1 mmol of ligand 5-(1H-pyrazol-3-yl)isophthalic acid and 0.1 mmol of metal salt Gd(NO3)3·6H2O in 10 mL of deionized water to obtain a mixed solution, add NaOH solution to adjust the pH value of the mixed solution to 7.0, and then transfer the mixed solution to a high-pressure reactor. After the temperature in the high-pressure reactor is increased to 180°C at a heating rate of 10°C / h, a solvent thermal reaction is carried out for 5 days to obtain a reaction product.
[0062] S2. The reaction product obtained in S1 is cooled and crystallized naturally, and then washed with anhydrous ethanol and filtered under reduced pressure to obtain a white crystalline powder, which is placed in an oven at a temperature of 60° C. for 3 hours for drying to obtain a lanthanide metal coordination polymer, a gadolinium (III) coordination polymer [Gd(piac)2(H2O)2] n , with a yield of 40.9%.
[0063] Example 9
[0064] The terbium (III) coordination polymer prepared in Example 3 and the gadolinium (III) coordination polymer prepared in Example 5 were further characterized as follows:
[0065] (1) Crystal structure determination of lanthanide metal coordination polymers
[0066] A single crystal of a coordination polymer with a clean and smooth surface, no concave surface, and no cracks was selected and the diffracted at 293(2)K using a BRDUKER SMARTAPEX-II CCDX-ray single crystal diffractometer with a graphite monochromatic Mo-Kα (wavelength ) rays, with The diffraction data were collected by scanning. All data were corrected by empirical absorption, and the crystal structure was solved by direct method. The anisotropy parameters and all non-hydrogen atom coordinates were corrected by least squares method. F2 was refined by SHELXTL-97 program, and the hydrogen atom coordinates were obtained by theoretical calculation method.
[0067] Detailed crystal determination data are shown in Tables 1 and 2, important bond length and bond angle data are shown in Tables 3 and 4, and the crystal structure is shown in Figure 1 to Figure 6 .
[0068] Table 1 Main crystallographic data of terbium (III) coordination polymerization
[0069]
[0070]
[0071] Where, R1 = ∑(||Fo|-|Fc||) / ∑|Fo|, wR2 = [∑w(Fo 2 -|Fc2 ) 2 / ∑w(Fo) 2 ] 1 / 2 ;
[0072] Table 2 Main crystallographic data of gadolinium (III) coordination polymers
[0073]
[0074]
[0075] Table 3 Important bond lengths of terbium (III) coordination polymers and bond angle (°)
[0076]
[0077]
[0078] Table 4 Important bond lengths of gadolinium (III) coordination polymers and bond angle (°)
[0079]
[0080]
[0081] In Table 1, a, b and c represent the edge lengths of the crystal in the directions of the three crystal axes, α, β and γ represent the angles between a and b, a and c, and b and c, respectively; Z is the number of molecules contained in the unit cell; the diffraction index range of the limiting factor is (h, k, l); F(000) is the number of electrons in the unit cell; Θ is the Θ angle range of data collection; FinalRindices[I>2σ(I)] is the residual factor R value for the observable diffraction point; R is the non-weighted consistency factor; R1 and wR2 are both weighted consistency factors;
[0082] In the first row of Table 3, Tb1 refers to Tb atom 1 in the terbium (III) coordination polymer single crystal, O5 refers to O atom 5 in the terbium (III) coordination polymer single crystal, and Tb1-O5 represents the bond length between Tb atom 1 and O atom 5, which is 2.280±2, with 2 being the standard deviation;
[0083] O5-Tb1-O2 represents the bond angle between O atom 5, Tb atom 1 and O atom 2, and its bond angle is 129.66±9;
[0084] The same applies to other data in the table.
[0085] The two complexes are isostructural two-dimensional structures. The terbium (III) coordination polymer and the gadolinium (III) coordination polymer are centered on terbium (III) and gadolinium (III), respectively, to form an octa-coordinate structure, which is coordinated and connected by the carboxyl oxygen atoms of the ligands to form a one-dimensional ring-chain structure, and the ring-chain structure is further bridged by ligands to form a two-dimensional structure.
[0086] (2) Phase purity characterization of lanthanide metal coordination polymers
[0087] The powders of terbium (III) coordination polymer and gadolinium (III) coordination polymer were characterized by XRD using Bruker / D8Advance instrument. The characterization results are shown in Figure 7 , it can be seen that it has reliable phase purity, which provides a guarantee for its fluorescence sensing application and photocatalytic organic dye degradation application.
[0088] Example 10
[0089] Weigh 2 mg of the ground terbium (III) coordination polymer prepared in Example 3 and immerse it in an equal volume of DMF solution containing different ions (M = NaNO3, KNO3, LiNO3, Hg(NO3)2, Cu(NO3)2, Pb(NO3)2, Zn(NO3)2, Cd(NO3)2, Mn(NO3)2 and Co(NO3)2) with a concentration of 1 mol / L. After ultrasonication, let it stand and take the clear supernatant for luminescence study at room temperature.
[0090] At an excitation wavelength of 345 nm, the emission intensity of the complex under different ions was measured. 2+ When the terbium(III) complex exists, the luminescence intensity of the complex is significantly reduced, which indicates that the terbium(III) complex has a 2+ There is obvious fluorescence quenching phenomenon, so Cu can be effectively detected by fluorescence quenching 2+ , the results are as follows Figure 8 and Fig. 9 shown.
[0091] Embodiment 11
[0092] 15 mg of the ground gadolinium (III) coordination polymer prepared in Example 5 was weighed and added to a 50 mL reactor, and 30 mg / L of rhodamine B (Rh B) and methyl orange solution (MO) were added to the reactor. After ultrasound, it was placed in a dark reaction box for a dark reaction of 30 min, and then the light was turned on for a reaction of 120 min.
[0093] Take 5 mL of the reaction solution every 15 minutes and measure its absorbance using a UV-visible light analyzer. Fig.10 As shown, it can be seen that the absorbance of rhodamine B and methyl orange decreases significantly when the gadolinium (III) coordination polymer exists.
[0094] This phenomenon indicates that the gadolinium (III) coordination polymer is a good photocatalyst that can effectively degrade rhodamine B and methyl orange. Fig.11 shown.
[0095] The above is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent change made to the above embodiment according to the technical essence of the invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A lanthanide metal coordination polymer, characterized in that: The chemical expression of the lanthanide metal coordination polymer is: [Gd(piac)2(H2O)2] n or [Tb(piac)2(H2O)2] n , where the ligand piac 2- is a deprotonated H2piac, wherein the H2piac is 5-(1H-pyrazole-3-yl)isophthalic acid, and the single molecular formulas of the lanthanide metal coordination polymer are C 22 H 17 N4O 10 Gd or C 22 H 17 N4O 10 Tb.
2. A method for preparing a lanthanide metal coordination polymer as claimed in claim 1, characterized in that: The following steps are involved: S1, dissolving 5-(1H-pyrazol-3-yl)isophthalic acid and a lanthanide metal salt in deionized water to obtain a mixed solution, adding a NaOH solution to adjust the pH value of the mixed solution, and then subjecting the mixed solution to a hydrothermal reaction to obtain a reaction product; S2. The reaction product obtained in S1 is cooled and crystallized naturally, and then washed and dried to obtain a lanthanide metal coordination polymer.
3. The method for preparing the lanthanide metal coordination polymer according to claim 2, characterized in that: The lanthanide metal salt in S1 is Gd(NO3)3·6H2O or TbCl3·6H2O.
4. The method for preparing the lanthanide metal coordination polymer according to claim 2, characterized in that: The molar ratio of 5-(1H-pyrazol-3-yl)isophthalic acid to lanthanide metal salt in S1 is 0.05-0.1 mmol: 0.1-0.15 mmol.
5. The method for preparing the lanthanide metal coordination polymer according to claim 2, characterized in that: The pH value of the mixed solution in S1 is 5-7.
6. The method for preparing the lanthanide metal coordination polymer according to claim 5, characterized in that: The temperature of the hydrothermal reaction in S1 is 180° C., the temperature rise rate in the hydrothermal reaction is 5 to 10° C. / h, the hydrothermal reaction is carried out in a sealed reactor, and the time of the hydrothermal reaction is 3 to 5 days.
7. The method for preparing the lanthanide metal coordination polymer according to claim 2, characterized in that: The drying conditions in S2 are: drying in a constant temperature drying oven at 60° C. for 3 h.
8. A use of the lanthanide metal coordination polymer according to any one of claims 1 to 7, characterized in that: The lanthanide metal coordination polymer can be applied to the field of fluorescent ion detection and the field of photocatalytic organic dye degradation.
Citation Information
Patent Citations
Fluorescent MOFs ink as well as preparation method and application thereof
CN114350207A
Three-dimensional ionic yttrium (III) coordination polymer as well as preparation method and application thereof
CN114381010A
Two-dimensional binuclear terbium coordination polymer as well as preparation method and application thereof
CN114672038A
Pyrazole carboxylic acid rare earth MOF luminescent material and preparation and application thereof
CN116574266A
Two-dimensional lanthanide series metal-organic framework material as well as preparation method and application thereof
CN119264456A